Health Care Workers’ Experiences on Childbirth Complications and their Risk Factors in Mogadishu, Somalia - Abdi-Soojeede, Mohamed Ibrahim; Alasow, Maryan Dahir (British Journal of Healthcare and Medical Research, 2023)
Introduction: Maternal mortality rates in Somalia are among the highest in the world, with women there having a one in 22 lifetime risk of dying during pregnancy. Objective: the objective of this study was to investigate worker’s experiences on childbirth complications and the risk factors that affects pregnant women who visit health facilities. The research's driving questions were, "What are the most frequent problems during childbirth in Mogadishu, Somalia?" What do medical professionals anticipate as the potential Risk factors of delivery complications? Materials and Methods: The study's cross-sectional assessment of health worker’s experiences on childbirth complications and their risk factors were planned to be gathered from data at a specified group of healthcare facilities in Mogadishu, Somalia, The study's target population consisted of 78 health workers who were asked to respond to childbirth complications; 65 participants were chosen using non-probability methods. The questionnaires were used, and then analyzed in excel and SPSS into frequency table and descriptive statistics (Mean and standard deviations). Results: The significance of discovering the highest percentage that was a Health worker’s experiences on childbirth complication in Mogadishu, Somalia, including "labor that does not progress (prolonged labor)," which is 67.7% of respondents who strongly agreed and agreed the existence of this complication at the Mogadishu maternal health center. The second highest percentage was "water breaking early (preterm PROM)," with 60% of respondents strongly agreeing or agreeing that this was a common childbirth complication.". Besides the risk factors with the highest percentage, "having sexually transmitted diseases and infections" 61.6% of those polled strongly agreed or agreed. The second question with the highest percentage in risk factors on childbirth complication is "Lack of near health services facilities," which has a score of 58.5%, which indicates the existence of unequally distributed health services in the community. Conclusion: The most frequent birthing complications were water breaking early (preterm PROM) and labor that did not progress (prolonged labor). Additionally to the risk factors with the highest percentages, "having sexually transmitted diseases and infections" and "Lack of near health services facilities," which point to the presence of a high percentage of STDI and unequally distributed health services in the community, respectively. Recommendation: The communities must have a fair distribution of health centers that are either free or low-cost and to increase health service utilization, health professionals must conduct a community-wide health awareness campaign.